2019
DOI: 10.1097/md.0000000000016597
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prostaglandin analogues in primary open-angle glaucoma or ocular hypertension patients

Abstract: Background: To evaluated and compared the efficacy and safety of 3 prostaglandin analogues (0.005% latanoprost, 0.004% travoprost, and 0.03% bimatoprost) in treatment of primary open-angle glaucoma (POAG) or ocular hypertension (OHT). Methods: PubMed, Embase, Cochrane library, Web of science, CNKI, Wanfang, and Vip database, published between January 1, 2000 and June 1, 2018, were systematically examined for randomized controlled trials (RCT) based on prostaglandin anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 37 publications
2
35
1
1
Order By: Relevance
“…In the current study, the IOP decrease at 3 months after initiating or starting treatment was similar between groups, indicating a similar efficacy of the preserved and preservative-free formulations. The change in IOP is similar to previous publications of PCL [ 27 ]. Some have postulated that the disruption of the corneal epithelium by preservatives may allow greater therapeutic efficacy of topical ophthalmic medications [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the IOP decrease at 3 months after initiating or starting treatment was similar between groups, indicating a similar efficacy of the preserved and preservative-free formulations. The change in IOP is similar to previous publications of PCL [ 27 ]. Some have postulated that the disruption of the corneal epithelium by preservatives may allow greater therapeutic efficacy of topical ophthalmic medications [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…18,49 A recently published meta-analysis has shown that all prostaglandin analogues demonstrated a high incidence of conjunctival hyperemia. 53 Surprisingly, the data in this current study showed improvement of redness symptom, but the clinical sign of conjunctival hyperemia still unchanged. This may explain that the patients felt more comfortable after changing to preserved tafluprost and PF-tafluprost.…”
Section: Discussioncontrasting
confidence: 61%
“…It was recently reported that latanoprost eye drop causes cutaneous blistering rash of eyelids, the neck and dorsum of hands, which resolved with cessation of treatment [42]. A meta-analysis by Tang et al, observed that latanoprost was better tolerated compared to travoprost or bimatoprost [43]. Conjunctival hyperaemia occurs more frequently with bimatoprost and travoprost whereas more patients experienced growth of lashes compared to latanoprost.…”
Section: B) Adverse Effectsmentioning
confidence: 99%